Analisis Efisiensi Faktor-Faktor Produksi Pada Usahatani Tebu - Andhika Ayu Anggrainingrum; Edy Prasetyo; Wiludjeng Roessali (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2022)
ENGLISHPati Regency is one of the sugarcane production centers in Central Java. The purpose of this study is to analyze the effect of the use of production factors on sugarcane production and analyze the level of technical efficiency, allocative efficiency and economic efficiency of the use of production factors in sugarcane farming. The research was conducted from May-July 2021 in Kayen District, Pati Regency. The research used methods of survey and interviews. Determination of respondents were conducted by the census. Respondents including 53 farmers are the total number of sugarcane farmers in Kayen District. The effect of production factors on sugarcane production was analyzed using multiple linear regression with the Cobb-Douglass production function. Technical efficiency used Maximum Likelihood estimation. Allocative efficiency was analysed through the comparison of the value of the marginal product with the price of the input. Economic efficiency is the result of the multiplication of technical efficiency with allocative efficiency. The results showed that technical efficiency had been achieved in the input of land area, seeds, organic fertilizers, ZA fertilizers and amegrass pesticides which showed a significant effect on sugarcane production in Kayen District, Pati Regency. Inputs that have not achieved allocative efficiency are land area, seeds, ZA fertilizer, and amegrass pesticides, while inputs that are not efficiently allocative are organic fertilizers. Multiplying the value of technical efficiency with price efficiency shows that the production factors of sugarcane farming in Kayen District are not yet efficiently economical. INDONESIAKabupaten Pati merupakan salah satu sentra produksi tebu di Jawa Tengah.Tujuan penelitian ini menganalisis pengaruh penggunaan faktor produksi terhadap produksi tebu dan tingkat efisiensi teknis, efisiensi alokatif dan efisiensi ekonomi penggunaan faktor-faktor produksi.Pemilihan lokasi dilakukan secara purposive.Metode penelitian yang digunakan adalah survei dan petani tebu dibakukan sebagai responden penelitian.Pengumpulan data dilakukan menggunakan metode wawancara berdasarkan kuesioner yang telah dipersiapkan.Responden penelitian ini diambil melalui sensus dengan jumlah responden sebanyak 53 petani. Pengaruh faktor produksi terhadap produksi tebu dianalisis menggunakan regresi linier berganda dengan fungsi produksi model Cobb-Douglas. Efisiensi teknis menggunakan pendugaan Maximum Likelihood. Efisiensi alokatif melalui perbandingan nilai produk marginal dengan harga input. Efisiensi ekonomi hasil perkalian efisiensi teknis dengan efisiensi alokatif.Hasil penelitian menunjukkan bahwa efisiensi teknis tercapai pada faktor produksi luas lahan, bibit, pupuk organik, pupuk ZA dan pestisida amegrass menunjukkan pengaruh signifikan terhadap produksi tebu di Kecamatan Kayen Kabupaten Pati. Faktor produksi yang belum mencapai efisiensi secara alokatif yaitu luas lahan, bibit, pupuk ZA, dan pestisida amegrass, sedangkan faktor produksi yang tidak efisiensi secara alokatif yaitu pupuk organik. Hasil perkalian nilai efisiensi teknis dengan efisiensi harga menunjukkan bahwa faktor produksi usahatani tebu di Kecamatan Kayen belum efisien secara ekonomi.